2023
DOI: 10.1136/jitc-2022-005319
|View full text |Cite
|
Sign up to set email alerts
|

Tasquinimod suppresses tumor cell growth and bone resorption by targeting immunosuppressive myeloid cells and inhibiting c-MYC expression in multiple myeloma

Abstract: BackgroundImmunotherapy emerged as a promising treatment option for multiple myeloma (MM) patients. However, therapeutic efficacy can be hampered by the presence of an immunosuppressive bone marrow microenvironment including myeloid cells. S100A9 was previously identified as a key regulator of myeloid cell accumulation and suppressive activity. Tasquinimod, a small molecule inhibitor of S100A9, is currently in a phase Ib/IIa clinical trial in MM patients (NCT04405167). We aimed to gain more insights into its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Tasquinimod, an inhibitor of S100A9, is currently in a phase Ib/IIa clinical trial in multiple myeloma patients (NCT04405167). A recent study demonstrated that Tasquinimod could inhibit the MDSC suppressive ability and promote T cell activation in myeloma BM microenvironment ( 85 ). As we showed, the TME of the high-risk group were immune suppressive with higher MDSCs and Tregs infiltration and poor immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Tasquinimod, an inhibitor of S100A9, is currently in a phase Ib/IIa clinical trial in multiple myeloma patients (NCT04405167). A recent study demonstrated that Tasquinimod could inhibit the MDSC suppressive ability and promote T cell activation in myeloma BM microenvironment ( 85 ). As we showed, the TME of the high-risk group were immune suppressive with higher MDSCs and Tregs infiltration and poor immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%